The Potency of the Genus Uncaria from East Borneo for Herbal Medicine Purposes: A Mini-review - Maria Almeida; Supriatno Salam; Agung Rahmadani; Helmi Helmi; Angga Cipta Narsa; Sri Agung Fitri Kusuma; Sriwidodo Sriwidodo (Journal of Tropical Pharmacy and Chemistry, 2022)
Uncaria is a genus of plants that are widely distributed in the tropics. There are about 5 of the 38 species of this genus growing in the tropical rain forests of East Borneo, Indonesia. For a long time, Uncaria is commonly used as a traditional medicine to treat various diseases by the Dayak tribe in Kalimantan, traditional people believe that Uncaria may be cured cancer, tumors, mioms, and cycts. Based on previous studies, the activity of the genus Uncaria has been widely reported such as cytotoxic, antimicrobial, antioxidant, antidiabetic, and thrombolytic activities. This article aims to summarize the potential of the Uncaria genus, focusing on 5 species from East Borneo, namely Uncaria nervosa, Uncaria longiflora, Uncaria gambir, Uncaria tomentosa and Uncaria cordata. The method used in this article is a literature study by collecting previous research articles related to the Uncaria genus. The results of the literature study show that the Uncaria genus in East Borneo has many secondary metabolites with diverse chemical structures that show good biological potential so that they can be used as broad and promising insights for drug discovery and development. This paper is also expected to provide input for the policy of conservation of medicinal plants in the forests of East Borneo.